Ferdinando Fuga and Nicola Salvi: “Contro il Barocco” Architecture and the Threshold of Neoclassicism in the Italian Architecture in the First Half of the 18th Century - Sansieva, Anna V. (Actual Problems of Theory and History of Art, 2020)
Italian scientists in the works related to the architecture of the 18th century, deny the presence of buildings made directly in the neoclassical style in Italy up to the turn of the 18th‑19th centuries. However, the existing terms are trying to separate the architecture of the 18th century from the previous 17th century leaving it, nevertheless, within the Baroque line. The prominent representatives of this crucial period were the architects Ferdinando Fuga and Nicola Salvi. Their projects for the most important Roman competitions of 1732 (the facade of the Basilica San Giovanni in Laterano and the Trevi Fountain) vividly show the irreconcilable differences between the fading Baroque and the emerging neoclassical style, which these masters managed to combine completely individually according to their own attitude not only to architecture, but also to the era. Similar processes are manifested in realized building projects of the masters, particularly in the sacral architecture. However, it was the architecture of Nicola Salvi that was absorbed and understood by the contemporaries ready to perceive the emotionality of the Baroque. At the same time, it is the art of Ferdinando Fuga that exemplifies the architecture of the transition from Baroque to neoclassical intentions.
Keywords: Neoclassicism; Italian architecture; Trevi Fountain; Fuga; Salvi; basilica; sacral architecture; 18th century